2020
DOI: 10.1002/adem.202000291
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural and Thermal Characterization of 316L + WC Composite Coatings Obtained by Laser Cladding

Abstract: Herein, a metal matrix composite (MMC) composed of 316L stainless steel and 20% in volume of tungsten carbides (WC), fabricated by laser cladding (LC) is considered. LC is an additive manufacturing technique, characterized by ultrafast cooling rates and limited diffusion, thus giving rise to out-of-equilibrium microstructures. The microstructure of the MMC is found to consist of partially dissolved WC well distributed in an austenitic matrix reinforced by a network of reaction carbides. Those mixed reaction ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 37 publications
0
9
0
1
Order By: Relevance
“…As for AISI 316 L stainless steel layers, it has been reported that the properties of the cladding layers were improved by compositing with SiC, TiC and titanium carbonitride [18][19][20]. As a matter of course, the WC particles composite for AISI 316 L stainless steel layers obtained by the laser cladding process also leads to improved mechanical properties, in particular, surface hardness and wear resistance [21][22][23]. During the heating of the laser cladding process, the WC particles decompose and solidify in the AISI 316 L steel matrix, and consequently, the steel matrix structure modifies to form carbide networks as a dendritic structure [21,22,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for AISI 316 L stainless steel layers, it has been reported that the properties of the cladding layers were improved by compositing with SiC, TiC and titanium carbonitride [18][19][20]. As a matter of course, the WC particles composite for AISI 316 L stainless steel layers obtained by the laser cladding process also leads to improved mechanical properties, in particular, surface hardness and wear resistance [21][22][23]. During the heating of the laser cladding process, the WC particles decompose and solidify in the AISI 316 L steel matrix, and consequently, the steel matrix structure modifies to form carbide networks as a dendritic structure [21,22,24].…”
Section: Introductionmentioning
confidence: 99%
“…As a matter of course, the WC particles composite for AISI 316 L stainless steel layers obtained by the laser cladding process also leads to improved mechanical properties, in particular, surface hardness and wear resistance [21][22][23]. During the heating of the laser cladding process, the WC particles decompose and solidify in the AISI 316 L steel matrix, and consequently, the steel matrix structure modifies to form carbide networks as a dendritic structure [21,22,24]. In addition, WC, W 2 C phases, M 23 C 6 , and (Fe,W) 3 C complex carbide phases form, and tungsten and carbon elements solidify [25].…”
Section: Introductionmentioning
confidence: 99%
“…Reports are also available to develop metal matrix composite coating by laser cladding technique [16][17][18][19][20][21][22][23][24][25][26][27]. Tehrani et al [16] developed WC-Ni composite coating by electroless plating of WC on Ni and its laser melting using Nd:YAG laser.…”
Section: Introductionmentioning
confidence: 99%
“…316L stainless steel is a typical low-carbon austenitic stainless steel with good mechanical properties and excellent corrosion resistance, which is widely used in aerospace, chemical, nuclear industry, and marine engineering [ 1 , 2 , 3 , 4 ]. However, due to its weak hardness and wear resistance, its application is greatly limited [ 2 ].…”
Section: Introductionmentioning
confidence: 99%